2022
DOI: 10.24171/j.phrp.2022.0122
|View full text |Cite
|
Sign up to set email alerts
|

Safety monitoring of COVID-19 vaccination among adolescents aged 12 to 17 years old in the Republic of Korea

Abstract: Objectives: This study aimed to disseminate information on coronavirus disease 2019 (COVID-19) vaccine safety among adolescents aged 12 to 17 years in the Republic of Korea.Methods: Two databases were used to assess COVID-19 vaccine safety in adolescents aged 12 to 17 years who completed the primary Pfizer-BioNTech vaccination series. Adverse events reported to the web-based COVID-19 vaccination management system (CVMS) and collected in the text message-based system were analyzed.Results: From March 5, 2021 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…1 ; Supplemental Table 2 ). Eventually, 15 observational studies [6] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] met the inclusion criteria ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ; Supplemental Table 2 ). Eventually, 15 observational studies [6] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] met the inclusion criteria ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 15 included studies were summarized in Table 1 . Briefly, 12 were used for the overall and subgroup analyses [6] , [12] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [23] , [24] , [25] , 2 for the overall analyses [13] , [14] , and 1 for the subgroup analyses only [22] . One study [13] focused on both BNT162b2 (Pfizer-BioNTech) and mRNA-1273 (Moderna) vaccines, and 14 [6] , [12] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] on BNT162b2 (Pfizer-BioNTech) vaccines alone.…”
Section: Resultsmentioning
confidence: 99%
“…7 8 This milder clinical course of VAM in an East Asian population compared with other ethnicities is consistent with other studies on Asian populations. 12 14 19 These limited but consistent results imply that VAM in the East Asian adolescent population may have a similar or even milder clinical course than in other populations.…”
Section: Discussionmentioning
confidence: 73%
“…Coronavirus disease 2019 (COVID- 19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in 500 million confirmed cases and 6 million deaths worldwide and was declared as a pandemic on March 11, 2020, by the World Health Organization. 1,2 The vaccine efficacy on COVID-19, including the omicron variant, has been reported to be 70 to 85% in the early phase and more than 50% in the subsequent stage.…”
Section: Introductionmentioning
confidence: 99%
“…11 KDCA reviewed AEs in adolescents aged 12–17 reported through February 2022. 78 Out of 12,216 AEs, there were 85 suspected cases of anaphylaxis, 74 suspected cases of myocarditis/pericarditis, 2 cases of suspected multisystem inflammatory syndrome, and 2 deaths. The KDCA concluded that the deaths were unrelated to vaccination.…”
Section: Adverse Events Of Covid-19 Vaccines In Koreamentioning
confidence: 99%